Study on key technologies of unmanned driving shearer - ZHANG Hao; GE Shirong (Gong-kuang zidonghua, 2016)
The paper described technical architecture of unmanned driving shearer from aspects of recognition system, decision-making system and control system. It discussed key technologies of unmanned driving shearer and their breakthrough directions, including autonomous positioning technology of shearer, autonomous correction technology of shearer, coal-rock interface recognition technology and autonomous obstacle avoidance technology of shearer, considered multi-sensor fusion technology could improve accuracy and reliability of autonomous positioning and navigation of shearer, and provide technical idea to solve key problems of unmanned driving shearer.